Bioeconomic and environmental valuation of dipterocarp estate forest based on local wisdom in Kutai Kartanegara, Indonesia - MUS MULIADI; ABUBAKAR M. LAHJIE; B. D.A.S. SIMARANGKIR; YOSEP RUSLIM (Society for Indonesian Biodiversity, 2017)
Abstract. Muliadi M, Lahjie AM, Simarangkir B.D.A.S., Ruslim Y. 2017. Bioeconomic and enviromental valuation of dipterocarp estate forest based on local wisdom in Kutai Kartanegara, Indonesia. Biodiversitas 18: 401-408. Research was conducted in the dipterocarp estate forest in Kutai Kartanegara District, East Kalimantan Province, Indonesia and aimed (i) to find out the potentials of logs; (ii) to find out the correlation among variables based on bioeconomic and environmental analysis; (iii) to analyze the value of bioeconomic and environmental equilibrium; (iv) to find out the price of logs based on local wisdom. Findings showed that bioeconomic analysis based on local wisdom in dipterocarp plantation forest at different estating distance had different potential and increment, while the same maximum increment was found at 40 years and their equilibrium was found at 30 years. Other local wisdom also showed there was a strong relationship between bioeconomic and environmental variables. Diameter influenced the price of logs and local wisdom suggested higher than the market prices at the diameter of 35 cm at 230.50 USD, while the price of log in the market was actually 145 USD. Thus the unpaid environmental services amounted to 85.5 USD m-3. Therefore the government should change the amount of the current levy. If there is no change, the government will not be able to finance the restoration of estate forest and natural forest and have further impacts on climate change. Keywords: Bioeconomic and environmental valuation, dipterocarp estate forest, local wisdom